Activation of the Pyrin Inflammasome by Intracellular Burkholderia cenocepacia - Gavrilin, Mikhail A. (2012)
Burkholderia cenocepacia is an opportunistic pathogen that causes chronic infection and induces progressive respiratory inflammation in cystic fibrosis patients. Recognition of bacteria by mononuclear cells generally results in the activation of caspase-1 and processing of IL-1β, a major proinflammatory cytokine. In this study, we report that human pyrin is required to detect intracellular B. cenocepacia leading to IL-1β processing and release. This inflammatory response involves the host adapter molecule ASC and the bacterial type VI secretion system (T6SS). Human monocytes and THP-1 cells stably expressing either small interfering RNA against pyrin or YFP–pyrin and ASC (YFP–ASC) were infected with B. cenocepacia and analyzed for inflammasome activation. B. cenocepacia efficiently activates the inflammasome and IL-1β release in monocytes and THP-1. Suppression of pyrin levels in monocytes and THP-1 cells reduced caspase-1 activation and IL-1β release in response to B. cenocepacia challenge. In contrast, overexpression of pyrin or ASC induced a robust IL-1β response to B. cenocepacia, which correlated with enhanced host cell death. Inflammasome activation was significantly reduced in cells infected with T6SS-defective mutants of B. cenocepacia, suggesting that the inflammatory reaction is likely induced by an as yet uncharacterized effector(s) of the T6SS. Together, we show for the first time, to our knowledge, that in human mononuclear cells infected with B. cenocepacia, pyrin associates with caspase-1 and ASC forming an inflammasome that upregulates mononuclear cell IL-1β processing and release.